The Ineffectiveness of Mediation in Divorce Disputes: A Case Study in the Palembang Religious Court - Sri Turatmiyah; Joni Emirzon; Annalisa Y; Haniyatul Husna binti Md Mohtar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2022)
Abstract: This article examines the ineffective of the mediation process in divorce disputes at the Palembang Religious Court during the period from 2020 to 2022. Data was collected through observations, documentation, and interviews with litigants and judges involved in divorce cases at the Palembang Religious Court. Relying on the legal effectiveness theory, the study found that over a span of three years (2020, 2021, and 2022), the Palembang Religious Court successfully mediated only 33 divorce disputes (0.45%) out of a total of 7,338 cases. This indicates that mediation of divorce disputes at the court has not been effectively implemented. The article also reveals several factors contributing to this ineffectiveness, including (1) the complex background and reasons for the parties involved in the disputes, (2) an imbalance between the number of mediator judges and the number of cases brought to the court, (3) a lack of good faith on the part of the parties to engage in the mediation process, (4) inadequate resources and facilities, and (5) a low legal culture and poor legal awareness among the litigants. These findings reinforce the results of previous research on the ineffectiveness of mediation in divorce lawsuits in various courts across Indonesia.Abstrak: Artikel ini mengkaji problem tidak efektifnya proses mediasi sengketa perceraian di Pengadilan Agama Palembang selama rentang waktu 2020 hingga 2022. Data dikumpulkan melalui observasi, dokumentasi dan wawancara dengan sejumlah narasumber, baik yang berperkara maupun yang menangani perkara perceraian di Pengadian Agama Palembang. Penelitian ini menemukan bahwa dalam kurun waktu tiga tahun (2020, 2021 dan 2022), Pengadilan Agama Palembang hanya berhasil memediasi 33 sengketa perceraian (0.45%) dari total 7.338 sengekta perceraian. Hal ini membuktikan bahwa mediasi sengketa perceraian di Pengadilan Agama Palembang belum berjalan secara efektif. Artikel ini juga menemukan bahwa penyebab tidak efektifnya proses mediasi di Pengadilan Agama Palembang, yakni (1) kompleksnya latar belakang alasan para pihak yang bersengketa atau mengajukan perceraian, (2) tidak berimbangnya rasio jumlah hakim mediator dengan banyaknya jumlah perkara yang masuk ke pengadilan, (3) tidak adanya itikad baik dari para pihak untuk melakukan proses mediasi, (4) sarana dan fasilitas yang tidak memadai, dan (5) budaya hukum yang rendah dan minimnya pengetahuan dan kesadaran hukum di kalangan para pihak yang bersengketa. Temuan ini menguatkan hasil penelitian-penelitian sebelumnya tentang tidak efektifnya mediasi dalam sengketa perceraian di berbagai Pengadilan di Indoensia. Keywords: The effectiveness of mediation; divorce disputes; the Palembang Religious Court